Integrated Climatic and Environmental Analysis for Sustainable Infrastructure Planning: A Case Study of Pioneer Airport Development in Central Papua, Indonesia - Anugrah Anugrah; Hartina Harun; Tustiyana Windiyani; Poppy Indrayani; Ritnawati Ritnawati; Suwardi Setiawan; Fatmeriany Fatmeriany; Irfan Syarifandy; Yu Cai; Suman Manandhar (Universitas Trisakti, 2026)
Aim: This study aims to evaluate potential environmental impacts associated with the construction of the Hoya Pioneer Airport in Central Papua, Indonesia, with particular emphasis on climatological characteristics and their implications for sustainable infrastructure development and surrounding residential environments. Methodology and results: The study employs climatological analysis focusing on rainfall patterns at the project site. Rainfall classification was conducted using the Schmidt and Ferguson method, which categorizes climatic conditions based on the average number of wet, humid, and dry months. Wet months are defined by rainfall exceeding 100 mm, dry months by rainfall below 60 mm, and humid months by rainfall ranging between 60-100 mm. The analysis indicates that the study area is characterized by high rainfall intensity, which may influence land stability, erosion potential, drainage system requirements, and construction feasibility. These findings highlight the necessity of integrating climatological considerations into environmental management planning for airport infrastructure development. Conclusion, Significance, and Impact: The development of the Hoya Pioneer Airport is expected to enhance regional connectivity, accessibility, and socio-economic growth, particularly in previously isolated areas. Nevertheless, construction activities may pose environmental risks, including land degradation, habitat disturbance, and increased carbon emissions. Therefore, the implementation of sustainable construction practices, environmentally responsible management strategies, and climate-adaptive infrastructure planning is essential to minimize environmental impacts while maximizing socio-economic benefits for local communities and regional development.